«ПУШКИНСКИЙ ТЕКСТ» И «ДЯГИЛЕВСКИЙ ТЕКСТ»: «НАЧАЛО» И «КОНЕЦ» РУССКОЙ КЛАССИЧЕСКОЙ КУЛЬТУРЫ (Filološke pripombe, 2019)
The article deals with memoirs that describe the figure of impresario Diaghilev and his ballet company. The authors of the article consider literary works on Diaghilev as well as interpretations of these texts by critics and readers. The set of texts about Diaghilev is regarded as “Diaghilev text” which is compared with Pushkin text of Russian literature. The Diaghilev text reflects the Russian cultural life of the first half of the 20th century, the ideas of its authors connecting regulations and paradoxes of the Russian culture development in the context of the European culture. These texts claim crucial importance of hero personality activity for the 20th century of Russian and world literature. Among creators of Diaghilev text there were such authors, as A. Bely,A. Benua, A. Blok, Jan Cocteau, E. Diaghileva, M. Dobuzhinsky, M. Fokin,S. Grigoriev, T. Karsavina, M. Kshesinskya, M. Kuzmin, S. Lifar’, S. Makovsky,L. Myasin, N. Nabokov, B. Nizhinskaya, V. Nizhinsky, A. Ostroumova-Lebedeva,S. Prokofiev, F. Pulenk, M. Sert, I. Stravinsky, M. Tenisheva, N. Tikhonova,S. Volkonsky.Diaghilev text considers a person as a creator of a new culture; it has a tendency to mythologize a biography and activity of the main protagonist. All these features draw together Diaghilev text and Pushkin text. The main peculiarity of the Diaghilev text is that the life of protagonist has been created according to principles of the literary work construction. This text is set with a plot in which participants of the events play assigned roles.Views of the contemporaries on Diaghilev are defined by the early 20th centuryideas about “the business man” and “superman”. Pushkin text describes the very beginning of the classical period in the Russian culture. Diaghilev text tells us how art canons established in the Russian culture of the 19th century ended in the 20th century.